Image analysis and recognition : 17th international conference, ICIAR 2020, PoÌ¹voa de Varzim, Portugal, June 24-26, 2020 : proceedings /: 17th international conference, ICIAR 2020, PoÌ¹voa de Varzim, Portugal, June 24-26, 2020 : proceedings. ([2020]) - Unknown
No abstract available